(untitled) (MODERN CONSTRUCTION AND ARCHITECTURE, 2023)
The task of developing of concrete for the bases of road clothing using secondary concrete aggregates is relevant for an economic and ecological reasons. The properties of concrete were compared with different types of coarse aggregate of 8-16 mm fraction: granite river gravel, secondary crushed stone from recycled reinforced concrete structures, secondary crushed stone from recycled brickwork and ceramic tiles. Three types of sand with a fraction of 0-4 mm were also used: quartz, secondary sand from recycled reinforced concrete structures, secondary sand from recycled brickwork. 2 series of experiments were conducted. During the first series of experiments Portland cement CEM II/B-S 32.5 R and superplasticizer Soudal Soudaplast was used (1% from weight of cement). For the second series of experiments Portland cement CEM II/B-S 42.5 R and superplasticizer Berament HT28 was used (1.2% from weight of cement). The mobility of all mixtures was equal to S1. Concretes with Berament HT28 superplasticizer had a lower W/C ratio of mixture than concretes with similar aggregates composition and Soudal Soudaplast superplasticizer. The use of secondary crushed stone requires an increasing of the W/C ratio of the mixture. The simultaneous use of secondary sand additionally increases W/C. Due to the lower W/C, the concretes of the second series have a higher average density than the similar concretes of the first series of the experiment. Concretes based on granite gravel and quartz sand have the highest average density (2369-2465 kg/m3). When using secondary crushed stone from reinforced concrete structures, the average density decreases by 3-5%. When using secondary crushed stone from brickwork and ceramic tiles – decreases by 8-9%. Concretes based on secondary crushed stone and sand from reinforced concrete structures have a 6-9% lower average density compared to concretes on granite gravel. Concretes based on secondary crushed stone and sand from recycled brickwork and ceramic tiles have the lowest average density – from 2015 to 2061 kg/m3. Due to the use of higher grade cement and a more effective superplasticizer, the strength of the concretes of the second series of the experiment at the age of 3 days was 69-190% higher than the strength of similar concretes of the first series, at the age of 28 days – higher by 67 to 147%. When using quartz sand, concrete based on secondary crushed stone from reinforced concrete structures has the greatest strength. At the age of 3 days up to 17.97 MPa and 30.33 MPa, at the design age (28 days) up to 32.07 and 53.41 MPa for the first and second series, respectively. The lowest strength (about 16 MPa in the first series of experiments and 27 MPa in the second) had concretes using only low-strength secondary aggregates from recycled brickwork and ceramic tiles. In general, all the studied concretes on secondary aggregates were characterized by sufficient strength for their use in the bases of hard road clothes.